Participatory Guarantee Systems: structure, benefits and reasons for participation – insights from the Italian case study of Campi Aperti - Winkler, Greta; Kaufmann, Sonja; Hruschka, Nikolaus; Vogl, Christian R. (Frontiers in Sustainable Food Systems, 2024)
Participatory Guarantee Systems (PGS) have emerged from initiatives introduced by farmers and civil society to ensure the organic quality of products by directly involving producers, consumers, and other stakeholders in the guarantee process. While actor participation in PGS provides the foundation for these systems, it also presents challenges, yet little empirical research on this has been undertaken. This study used a framework to analyze four dimensions of participation in PGS: who, how, what kind, and why? The Italian case study of Campi Aperti was qualitatively and quantitatively analyzed by means of: (1) research of internet documents, (2) semi-structured interviews with seven key members and one expert, and (3) an online survey of PGS members (N = 614 members, survey sample: n = 16 producers and 45 co-producers). Participation took the form of two main activities: management of the guarantee process and organization of farmers’ markets. Discussions are held and decisions made at assemblies and market meetings. The growing number of producers joining the PGS has added to organizational tasks, and hence increased costs. Participants stated that the reasons for joining the Campi Aperti PGS and the benefits of being a member were to gain access to city markets and to send a political message. Building trust between members was an additional benefit cited. Time constraints emerged as the main drawback preventing participation by members, with producers taking on more roles and investing more time in the PGS than co-producers. However, co-producers provided evidence of other ways in which they participated in the PGS, in particular by making purchases and socializing at the markets.